2019
DOI: 10.5590/jerap.2019.09.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Curriculum in a Special Education Context: The Case of Individuals With Autism

Abstract: This article examines the issue of hidden curriculum as it pertains to the experiences of individuals with disabilities, primarily those diagnosed with autism disorders. Examining the assumptions regarding the hidden curriculum, this article explores the challenges these assumptions create for individuals with autism. We provide suggestions for how these challenges could be overcome through the use of specific strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Some key challenges for implementing distance learning for students with autism were noted, including lack of ICT technology, poor internet access, lack of teacher and caregiver training, social, communicative, and behavioral challenges that characterize students with autism. Nevertheless, distance learning offers immense opportunities for improving educational outcomes for students with autism, such as more individualized instruction programs, lack of social pressure, and being in a more comfortable learning environment (Sulaimani & Gut, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some key challenges for implementing distance learning for students with autism were noted, including lack of ICT technology, poor internet access, lack of teacher and caregiver training, social, communicative, and behavioral challenges that characterize students with autism. Nevertheless, distance learning offers immense opportunities for improving educational outcomes for students with autism, such as more individualized instruction programs, lack of social pressure, and being in a more comfortable learning environment (Sulaimani & Gut, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The home-based learning environments should be appropriately structured to create a safe learning environment that increases student attention and academic achievements. This can be achieved by working closely with the caregivers by creating learning spaces with all the required infrastructure and supportive learning tools, and one that is free from distractions (Sulaimani & Gut, 2019).…”
Section: Strategies For Creating Effective Distance Learning Educatiomentioning
confidence: 99%
“…Any learning must involve students being given the space to produce information across various disciplines and incorporate various perspectives. It is the role of educators to foster relevant skills in the process of learning, and most importantly impart skills such as critical thinking, problem solving, use of imagination, self-expression, and creativity (Duvall, 2020;Pink, 2006;Runco & Pritzker, 2020;Sulaimani, & Gut, 2019). Most online courses and distance education strategies have been able to embrace technologies and adapt their pedagogical approach to build on these personal and professional competencies among students thereby continuing to prepare them for the future (Cheng, 2006;Kaiper-Marquez, et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although development of professional ethics among students is one of the responsibilities of medical education,[ 1 ] researchers recommend putting students in the situations of simulated but realistic moral dilemma and uses cooperative learning strategies in teaching, including real-life stories, illustrations, and role-playing games,[ 4 ] and additional strategies that support social development of students including mobile learning, cooperative learning, and other forms of peer-mediated instruction. [ 5 6 7 ] Studies have shown that the teaching method employed to teach professional ethics to the medical students is lecturing, and the learning assessment method is paper-based examination run at the end of the term, and that there is no specific standard for teaching professional ethics. [ 8 ] Despite the fact that medical ethics and professionalism are taught to medical students, they perform unethical behaviors, so it is necessary to modify the method used for teaching professional ethics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] The hidden curriculum involves the unspoken cultural and social knowledge students acquire in the learning environment. [ 5 ] Studies have mainly reported the negative effects of the hidden curriculum. Some communicative aspects attributed to the hidden curriculum are related to the informal curriculum.…”
Section: Introductionmentioning
confidence: 99%